'I am a single mum. I don't feel like I can be as competitive as other people': experiences of precariously employed staff at UK universities. (1st April 2018) - ,
Abstract : Universities play a central role in informational capitalism. However, higher education institutions have undergone economic, political and cultural transformations leading to competition, market orientation and new management forms. These changes have effects on many levels, including the working conditions and practices of individuals involved in the information gaining process. This article aims to find out how the existing working conditions and practices at universities form the meanings, identities and experiences of individuals by focusing on precariously employed academics. I address this question based on a theoretical analysis and qualitative interviews with casualised academic staff.